STUDI NITRIFIKASI TANAH DENGAN PENAMBAHAN SERESAH ASAL HUTAN ALAMI DAN AGROFORESTRI KOPI - Anita Kismi Qifli; Kurniatun Hairiah; Didik Suprayogo (Jurnal Tanah dan Sumberdaya Lahan, 2014)
Forest conversion to coffee agro forestry has decreased quality and amount of litter fall, increase decomposition rate and litter fall mineralization. This research was aimed measuring soil nitrification rate by addition of forest, coffee based agro forestry with mix shade trees and legume-shaded coffee (Gliricidia sepium) and monoculture of coffee litter fall. This research that was conducted in May-June 2005 used InceptisolÂ  and litter fall of forest, coffee based agro forestry with mix shade trees and legume-shaded coffee (Gliricidia sepium) and monoculture of coffee from Bodong, Sumberjaya, Lampung Barat. Litter fall was collected by litter trap. This research was compiled in a completely randomized design with aerobic incubation method during 8 week in laboratory by 5 treatment addition of forest, coffee based agro forestry with mix shade trees and legume-shaded coffee (Gliricidia sepium), monoculture of coffee litter fall and control (non litter fall addition). Measurement conducted adding litter fall and soil has incubation during 2 weeks. Soil nitrification rate determined by comparing concentration of NH4+ and NO3- after added of litter fall. Data analysis was used one-way. Result of research showed that (1) addition of litter fall has significant (p<0.01) to concentration of NH4+ and NO3- - and N-mineral of soil (2) addition of litter fall has significant (p<0.01) to NH4+ /NO3- ratio (3) addition of coffee monoculture litter fall has yield concentration of NO3- higher than forest and coffee based agro forestry with mix shade trees litter fall (4) addition of coffee monoculture litter fall has yield ratio of NH4+ and NO3- lower (0.1mg kg-1) than addition of forest litter fall (1mg kg-1), coffee based agro forestry with mix shade trees litter fall (0.4mg kg-1) and legume-shaded coffee (Gliricidia sepium) litter fall (0.8mg kg-1). This result of research indicated that adding litter fall like forest, coffee based agro forestry with mix shade trees and legume-shaded coffee (Gliricidia sepium) litter fall can depress soil nitrification rate until 96%.